Analisis Perbandingan Excess Return Jakarta Islamic Index dan Indeks Harga Saham Gabungan - Galishia Putry; Iman Sugema; Deni Lubis (Department of Islamic Economics, IPB University, 2014)
Indonesia Stock Exchange statistics show that Islamic stock trading reached a value of around 59 trillion rupiahs. The excalation index of JII (Jakarta Islamic Index) is not follow by an increase in market capitalization of stocks listed on the JII. This is the question for investor who want to know how it compares to the performance of Jakarta Composite Index (JCI). This study analyzes the excess return that represents the return expected by an investor after investing in certain assets using descriptive analysis and Ordinary least square (OLS) regression of Capital Asset Pricing Model (CAPM). The descriptive analysis showed that in the same risk-free rate, investors who invest in stocks listed in JII can expect a higher return than the return JCI, while regression analysis shows investors do not expect the JII’s excess return to be different from JCI’s. This suggests that the selection criteria used by Bapepam LK (now OJK) and Indonesia Stock exchange does not affect the performance of return JII.